First caddisfly species from Mexican amber (Insecta: Trichoptera) - Wichard, Wilfried; Kraemer, Mónica M.s.; Luer, Claus (Zootaxa, 2006)
The first 4 new species of caddisflies (Trichoptera) are described from Mexican amber: Culoptila aguilerai n. sp. (Glossosomatidae), Plectropsyche alvarezi n. sp. (Hydropsychidae), Antillopsyche mexicana n. sp. (Dipseudopsidae), and Xiphocentron chiapasi n. sp. (Xiphocentronidae). Culoptila, Plectropsyche, and Xiphocentron are typical members of the Neotropical fauna and the fauna of Mexico; they now are also represented in Miocene Mexican amber. The genus Antillopsyche, previously known from the Greater Antilles and from Dominican amber, is now reported from Mexican amber.